THE REASONABLENESS AND EFFECTIVENESS OF THE AMENDMENT TO SECTION 26 OF THE MAINTENANCE ACT 99 OF 1998 - B Batchelor (Obiter, 2018)
Section 26 of the Maintenance Act as amended by the Maintenance Amendment Act 38 of 2005 (hereinafter “Amendment Act”) is a key provision for enforcing maintenance orders in South Africa. Underpinning this provision is the need to ensure that children are protected from destitution and deprivation due to maintenance defaulters. Primarily, this section limits a maintenance defaulter’s access to credit by negatively affecting his or her credit rating. The utility and legality of this provision as a measure of enforcing maintenance orders has yet to be judicially tested in South Africa. Therefore, this article evaluates the reasonableness of the limitation of a maintenance payer’s fundamental rights in the light of foreign jurisdiction mechanisms for enforcing maintenance orders.